DIFFERENCES IN THE LEARNING OUTCOMES IN THE TRANSITION OF ONLINE TO OFFLINE DURING COVID-19 - Dinda Khaliza Balqis Tarmizi; Erwin (Jurnal Cakrawala Pendas, 2025)
In the midst of a pandemic like now, many aspects of life are experiencing drastic changes, including the education sector. These changes have various implications and often cause implementation problems if they cannot be rebalanced. Changes in student personality are very different from face-to-face learning before the pandemic. This study aims to determine student learning outcomes during the online learning process, to determine student learning outcomes during the process of learning offline, and to find out the difference in results study students from online learning to offline. The type of research used is descriptive qualitative with a case study model. The data were collected through observation, interviews, and documentation. The data analysis technique uses engineering analysis data, which Miles and Huberman model is used. It consists of three stages, namely reduction data, presentation data, and withdrawal conclusion. According to the result of this research, it can be concluded that students’ grades were decreasing during online learning. Students’ grades were increasing during offline learning. There was a significant difference in students’ grade outcomes between online and offline learning. Therefore, the Implication of this research is the learning condition can affect student outcomes. This research can be evaluated for teachers who are teaching both online and offline conditions.